We dream; we don’t remember - Rashad Bin Faizal (Nanyang Technological University, 2023)
“We dream; we don’t remember.” is a homage to my mother. Using old family photos, the work pieces together the different experiences of my mother into a structural collage. This allows me to contemplate the life my mother gave to me while being conscious of her lived experiences despite unforeseen tribulations. The structural nature of the work also allows me to reconfigure my mother’s figure and present them differently each time, mirroring my personal act of meditation and acknowledgment of her identity and presence as my mother. By layering each fragment of my mother’s figure into a structure that extends beyond the two- dimensional plane, the work pays tribute to the actuality and reality behind each fragment. It captures the life my mother has lived and persevered into her current selfhood. The work is a personal endeavour that hopes to encourage viewers to appreciate the life they live, while being grateful for family. Life is only once, live a wonderful life.